Determinant of Organizational Innovation: Literature Review - Rakhman, Sitti (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Organizational innovation is an important factor for companies to achieve more competitive performance. Understanding how innovation capabilities emerge, develop, and apply can make important managerial scientific contributions. This study investigates the results of the main study on the determinants of organizational innovation capability, suggests some theoretical propositions for further studies based on the literature review. This study aims to identify the determinants of organizational innovation capability and the context in which the study is conducted. We identified and analyzed 43 articles through content analysis via Google Scholar. This study presents several results of studies on innovation capability in organizations, which are divided into determinants, internal, external aspects, and a collection of propositions to guide a research project in depth in questions that will be tested in further research. This study also makes a practical contribution, as it shows in which context each study of the identified determinants of innovation capability is applied.